The future excess fraction of occupational cancer among those exposed to carcinogens at work in Australia in 2012 - Carey, Renee; Hutchings, S.; Rushton, L.; Driscoll, T.; Reid, A.; Glass, D.; Darcey, E.; Si, S.; Peters, S.; Benke, G.; Fritschi, L. (Elsevier Inc., 2017)
Background: Studies in other countries have generally found approximately 4% of current cancers to be attributable to past occupational exposures. This study aimed to estimate the future burden of cancer resulting from current occupational exposures in Australia. Methods: The future excess fraction method was used to estimate the future burden of occupational cancer (2012–2094) among the proportion of the Australian working population who were exposed to occupational carcinogens in 2012. Calculations were conducted for 19 cancer types and 53 cancer-exposure pairings, assuming historical trends and current patterns continued to 2094. Results: The cohort of 14.6 million Australians of working age in 2012 will develop an estimated 4.8 million cancers during their lifetime, of which 68,500 (1.4%) are attributable to occupational exposure in those exposed in 2012. The majority of these will be lung cancers (n = 26,000), leukaemias (n = 8000), and malignant mesotheliomas (n = 7500). Conclusions: A significant proportion of future cancers will result from occupational exposures. This estimate is lower than previous estimates in the literature; however, our estimate is not directly comparable to past estimates of the occupational cancer burden because they describe different quantities – future cancers in currently exposed versus current cancers due to past exposures. The results of this study allow us to determine which current occupational exposures are most important, and where to target exposure prevention.